Equilibrio ambiental en una obra de concesión vial (2015)
Road concessions in Colombia have meant progress for the country, with the understanding that the infrastructure has been growing rapidly and has become one of the fundamental pillars of development. However, despite existing measures to cover the environmental damage caused as a result of the implementation of the concession project, deteriorating the environment is remarkable and the impairment of nature has often been irreparable, this means that despite the role of the environmental license the impact on the environment is damaging, and it is seeking to complement existing conservation efforts at the national level, the research was performed as an alternative to keep in mind about what you do not safeguard the environmental license. Initiatives highway concession projects must be environmentally responsible, economically viable and socially adaptable under this parameter, auxiliary measures proposed are aimed at restoring the ecological balance and the preservation of natural resources from the dealer. The importance lies in recovering the environmental conditions that nature held before the construction of the road or at least greatly repair damage caused. This research highlights the major environmental problems arising from the construction of concessions, described the restoration process, presents the possible solutions to environmental problems and finally summarizes some of the challenges that will be faced by the environment in the future with the construction of The fourth generation of concessions.